2002
DOI: 10.1046/j.1365-2249.2002.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of T-cell subsets that contact tumour cells in colorectal cancer

Abstract: It has been known for decades that solid malignancies in humans are associated with an infiltrate of inflammatory cells. A number of studies have found a clear positive correlation between the density of the lymphoid infiltrate and the prognosis of the patient [1][2][3][4]. This, together with the partial oligoclonality of carcinoma-infiltrating T cells [5], indicates that local immune responses to the tumours are likely to be occurring, although the precise nature of the response, and the reason for the survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
4
15
0
Order By: Relevance
“…In this study, we found that both THY1 and PHLDA1 were upregulated in colon cancer tissue and both of them were statistically relevant to the patient's anemia. This finding together with other reports (26,27) hint that THY1 and PHLDA1 products are two surface molecules responsible for crosstalk between colon cancer and the immune system.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we found that both THY1 and PHLDA1 were upregulated in colon cancer tissue and both of them were statistically relevant to the patient's anemia. This finding together with other reports (26,27) hint that THY1 and PHLDA1 products are two surface molecules responsible for crosstalk between colon cancer and the immune system.…”
Section: Discussionsupporting
confidence: 85%
“…Further work is required to determine whether the upregulation of these two genes in colon cancer is related to tumor-infiltrating T cells (27) being recruited, leading to increased tumor cell necrosis and subsequent tumor mass bleeding and patients' anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas HVEM and TIGIT expressions were not markedly changed, PD‐1 expression increased dramatically in all IEL T‐cell subsets analysed. Importantly, this may indicate that the functional capacity of IELs in the colon is reduced as a result of the chronic inflammation, which may have implications for mucosal immune surveillance of gut infections and potentially local immune surveillance of developing cancer cells from the colonic epithelium . It can be speculated that PD‐1 is upregulated on the T‐cells as a self‐protective mechanism induced by the emerging cancer cells, especially considering the early upregulation of both PD‐L1 and PD‐L2 mRNA levels in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is that several of these genes have been implicated in CRC development previously. CD7 (cluster of differentiation 7) encodes for an antigen expressed on the surface of T cells, which is elevated in colorectal tumor-infiltrating lymphocytes (35). STRA13 , a bHLH transcription factor, has been found to be elevated in CRC tumor tissue (36).…”
Section: Discussionmentioning
confidence: 99%